2021
DOI: 10.3390/ijerph182413211
|View full text |Cite
|
Sign up to set email alerts
|

Four-Way Decomposition of Effect of Alcohol Consumption and Body Mass Index on Lipid Profile

Abstract: Background: Both obesity and alcohol consumption are strongly associated with dyslipidemia; however, it remains unclear whether their joint effect on lipid profiles is through mediation, interaction, or a combination of the two. Methods: In total, 9849 subjects were selected from the 2009 panel of China Health and Nutrition Survey (CHNS). A four-way decomposition method was used to validate the pathways of drinking and body mass index (BMI) on lipids (total cholesterol, TC; triglyceride, TG; low-density lipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A study showed that the alcohol dietary pattern, characterized by consumption of large amounts of alcoholic beverages, liver, chicken and fish, was associated with the prevalence of dyslipidaemia and its components ( 25 ). Another Chinese study showed that alcohol and obesity interact to have an effect on blood lipids ( 53 ). Our results are similar to the results of that study.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the alcohol dietary pattern, characterized by consumption of large amounts of alcoholic beverages, liver, chicken and fish, was associated with the prevalence of dyslipidaemia and its components ( 25 ). Another Chinese study showed that alcohol and obesity interact to have an effect on blood lipids ( 53 ). Our results are similar to the results of that study.…”
Section: Discussionmentioning
confidence: 99%